Tephrostratigraphic constraints on sedimentation and tectonism in the Whanganui Basin, New Zealand. Issue 2 (2nd April 2020) - Rees, Callum; Palmer, Julie; Palmer, Alan
ABSTRACT: In the following paper, we apply digital mapping techniques and tephrostratigraphy to correlate marker horizons across the Whanganui Basin, culminating in a new 1:25, 000 geological map of the central Rangitikei. This is achieved by (1) compilation of existing research, (2) correlation of major element glass shard datasets to known eruptive products and (3) completion of a three-year field survey. We update and refine existing stratigraphic correlations, focusing on two critical units within the basin succession; namely the Makirikiri Tuff (1.6 Ma) and Kaimatira Pumice Sand (1 Ma) formations. Okehu Group is proposed to cover all strata from Pakihikura to Potaka pumice. Rewa Pumice is placed within its own formation bridging the Makirikiri Tuff and Kaimatira Pumice Sand formations. Mapping and analysis facilitate placement of Coutts Creek Horizon within Rewa Formation. Sub-aerial surfaces and influxes of greywacke and volcaniclastic detritus from c. 1.6 Ma onward provide evidence for an alluvial plain developing at the foot of the uplifting, paleo-axial range. We suggest uplift in the paleo-axial range occurred contemporaneously with the onset of rhyolitic activity at Mangakino caldera (c. 1.6 Ma) so that the first influxes of fluvial conglomerate and volcaniclastics occur in close proximity within the eastern basin succession.